Mechanism of polyuria and natriuresis in atrioventricular nodal tachycardia. Issue 6449 (6th October 1984) - Canepa-Anson, R; Williams, M; Marshall, J; Mitsuoka, T; Lightman, S; Sutton, R
Abstract : A woman with tachycardia associated with polyuria was investigated. Electrophysiological analysis showed that the tachycardia was an atrioventricular nodal re-entrant tachycardia. Programmed stimulation was then used to provoke and sustain the tachycardia for 40 minutes. Polyuria, with an appreciable increase in free water clearance, was observed. This was associated with reduction in plasma and urinary arginine vasopressin concentrations. Appreciable natriuresis also developed. These results support the hypothesis that the polyuria with increased free water clearance and the natriuresis occurring during sustained tachycardia in man are due to inhibition of secretion of vasopressin and the release of natriuretic factor.